2009
DOI: 10.1111/j.1399-5448.2008.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between physical activity, sedentary behavior, and glycemic control in a large cohort of adolescents with type 1 diabetes: the Hvidoere Study Group on Childhood Diabetes

Abstract: Background:  The Hvidoere Study Group on Childhood Diabetes has demonstrated persistent differences in metabolic outcomes between pediatric diabetes centers. These differences cannot be accounted for by differences in demographic, medical, or treatment variables. Therefore, we sought to explore whether differences in physical activity or sedentary behavior could explain the variation in metabolic outcomes between centers. Methods:  An observational cross‐sectional international study in 21 centers, with demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
82
2
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 20 publications
11
82
2
7
Order By: Relevance
“…3 Moreover, overall glycemic control (measured with glycated hemoglobin, or A1C, levels) with exercise has shown mixed results in T1D studies, with some demonstrating benefits [5][6][7] and others no improvement in A1C following aerobic or resistance training. 8,9 For overall glycemic control to be enhanced, individuals with T1D are required to skillfully balance insulin dosing and food intake to maintain blood glucose levels in a more normal range before, during, and after exercise. [10][11][12][13] Although many obstacles to safe and effective exercise participation remain, present and future technologies should assist more people with T1D to become and remain physically active to improve their health and reduce the negative impact of diabetes on participation in competitive sports and activities.…”
Section: Original Articlementioning
confidence: 99%
“…3 Moreover, overall glycemic control (measured with glycated hemoglobin, or A1C, levels) with exercise has shown mixed results in T1D studies, with some demonstrating benefits [5][6][7] and others no improvement in A1C following aerobic or resistance training. 8,9 For overall glycemic control to be enhanced, individuals with T1D are required to skillfully balance insulin dosing and food intake to maintain blood glucose levels in a more normal range before, during, and after exercise. [10][11][12][13] Although many obstacles to safe and effective exercise participation remain, present and future technologies should assist more people with T1D to become and remain physically active to improve their health and reduce the negative impact of diabetes on participation in competitive sports and activities.…”
Section: Original Articlementioning
confidence: 99%
“…Aman and colleagues (1) found that a reduction of sedentary activities through an increase in physical activity was associated with improved glycemic control and reduced levels of HbA1c. Hence, it is important to diagnose the physical activity level and cardiorespiratory fitness of adolescents with T1D, once the engagement in regular physical activities is a part of their treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The definition of at least 30 minutes of physical activity leading to breathlessness has been used in The Health Behaviour in School-aged Children Questionnaires by WHO in healthy children conducted in 3-year cycles in over 30 countries (30) and by the international Hvidoere Study Group on Childhood Diabetes (18) We have limited our material to include data from 2010-2011 only. Within that time period, SWEDIABKIDS contains data on 7,144 children and adolescents, 7-18 years old, with type 1 diabetes and a total of 43,612 visits.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have focused on the correlation between physical activity and HbA1c. Some have succeeded in showing a significant HbA1c-lowering effect of physical activity (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), whereas others have failed do so (16)(17)(18)(19)(20)(21)(22). HbA1c is a main variable in pediatric diabetes care.…”
Section: Introductionmentioning
confidence: 99%